An Investigation of Service Operations Strategies: Evidence from Greek Service Organisations - Xakoustos, Georgios (2006)
With the service industry accounting for 70% of GDP in the United States (Daley et al. 1998) and the continuous growth of the service sector in every developing and developed country (Shugan, 1994), several studies have revealed the importance of the service sector and the significant aspects of service operations. The importance of services and the great evolution of the service industry require a cautious examination of all the issues related to services. This paper presents a study about services and in particular service operations strategies. The focal point of the research is the front office operations. Thus, two Greek companies from the service sector were examined to give the project a more reliable view about service operations. The findings of the project are remarkable as they exhibit the most significant aspects of service operations. The study essentially concludes that the service strategies of the examined organisations are typically based on the front office operations. Additionally, it summarises that these two companies provide flexible products, a variety of services and mainly use face-to-face interaction to serve customers.